A study to assess the knowledge regarding expressed breast milk among working mothers attending outpatient departments in a selected hospital at Mangaluru, Karnataka, India - Naik, Akshata N.; Halder, Lygia V.; Prathiba, G.; Kanagavalli, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Breastfeeding is the gold standard for infant feeding. Breastfeeding is essential for child survival and health. Employment is one of the most common barriers to discontinue breast feeding after childbirth. Expressed breast milk (EBM) serves as a practical solution for mothers who cannot be physically present to breastfeed due to work commitments. The aim of the study was to assess the knowledge regarding EBM and find the association between knowledge and their sociodemographic variables among working mothers attending outpatient departments in a selected hospital at Mangaluru, Karnataka, India. Methods: A non-experimental descriptive study. Purposive sampling technique was used to select 30 working mothers. Data was collected using a structured knowledge questionnaire. Data was analysed using descriptive and inferential statistics. Results: The study findings showed that the mean knowledge score with standard deviation was 12.76±3.58 and the mean knowledge score percentage was 42.5% regarding EBM. There was no significant association between mother’s knowledge level and sociodemographic variables. Conclusions: The study highlights the urgent need for educational programs and support systems to empower working mothers with the right knowledge regarding EBM and ensuring better nutrition and growth for their infants.